A CROSS-SECTORAL APPROACH TO STEM EDUCATION: A MULTI-PERSPECTIVE DESIGN - Zascerinska, Jelena; Aleksejeva, Anastasija; Zascerinskis, Mihails; Abjalkiene, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The complexity of the STEM education ecosystem at all the educational levels has been risen by the COVID-19 pandemic. The search for a sustainable ecosystem leads to the cross-sectoral approach to STEM education. A sustainable STEM education ecosystem is also characterized by the coherence between the STEM education levels. The research aims at creating a theoretical model of the multi-perspective design of STEM education within a cross-sectoral approach for identifying the implications for further research on the cross-sectoral STEM education. The qualitative research was carried out. Research data were collected through the analysis of published research works. Content analysis was used for the analysis of the collected data. The theoretical novelty of the cross-sectoral STEM education is indicated: the structure and phases of STEM Education implementation and multi-perspective design. The exploratory research allows widening the traditional boundaries of the STEM education (teacher-content-student) with the concepts of educational discipline, conceptual change, all language as the unity, the digitalised educational process, and the cross-sectoral approach. The research is novel in the implications for further research on the cross-sectoral STEM education..